Penanggulangan Penyelundupan Narkotika Jenis Sabu-Sabu di Desa Pulo Teungoh Kecamatan Meureubo Kabupaten Aceh Barat - Cut Tasya; Nila Trisna (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Smuggling 1.2 tons of methamphetamine type narcotics in Pulo Teungoh Village, Kec. Meurebo, Kab. Aceh Barat is an international syndicate. This attempt was thwarted by a number of members of the Directorate of Drug Investigation at the Metro Jaya Police. The data collection method used is a juridical approach, such as the results of interviews and research observations. The results showed that the factors that cause drug smuggling are economic factors in the family tend to someone to commit a crime, be it stealing, murder or drug abuse. In an effort to overcome this, the West Aceh district government through Customs and Excise will more often carry out sea route operations by involving the police team in collaboration with the port and tightening the entry and exit routes via sea so that narcotics smuggling cases are less likely to occur, which are often passed by sea.